216k views
0 votes
Let f(x) = 3x + 2 and g(x) =x - 3. Find f(x) - g(x). Question 3 options: 2x - 5 4x - 1 2x - 1 2x + 5

2 Answers

6 votes

Answer: f(x)-g(x)=2x+5

Step by step:

f(x) = 3x+2

g(x) = x-3

f(x)-g(x) = 3x +2 - (x-3) = 3x + 2-x+3=2x+5

User Antonok
by
5.5k points
3 votes

Answer:

The answer is 2x + 5.

Explanation:

Given,


f(x) = 3x + 2,


g(x) = x - 3,

So,


f(x) - g(x) = 3x + 2 - ( x - 3) ( By substitution )


= 3x + 2 - x + 3 ( By distribution property )


=2x + 5 ( By operating like terms )


\implies f(x) - g(x)=2x + 5

Hence, last option is correct.

User Telmo Costa
by
4.9k points